DMSP Production by Coral-Associated Bacteria - Felicity W.I. Kuek; Felicity W.I. Kuek; Felicity W.I. Kuek; Felicity W.I. Kuek; Felicity W.I. Kuek; Cherie A. Motti; Cherie A. Motti; Jia Zhang; Jia Zhang; Ira R. Cooke; Ira R. Cooke; Jonathan D. Todd; et al. (Frontiers in Marine Science, 2022)
Dimethylsulfoniopropionate (DMSP) is an important molecule in the marine sulfur cycle, produced in large amounts by corals and their dinoflagellate endosymbionts, Symbiodiniaceae. Although corals are known to harbour bacteria that can catabolise DMSP, the recent discovery of bacteria capable of producing DMSP in coastal and deep-sea environments raises the possibility of a bacterial contribution to the DMSP output of corals. Here, 157 bacteria associated with four common coral species were isolated and screened for their ability to produce DMSP by targeting dsyB, a key gene involved in DMSP biosynthesis. Approximately 9% (14 out of 157) of the bacterial isolates harboured dsyB, all being members of the Alphaproteobacteria. The ability of these isolates to produce DMSP was confirmed by liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR) measurements. A dsyB-harbouring strain, Shimia aestuarii AMM-P-2, was selected for genome sequencing. This strain harbours the complete genetic machinery to (i) assimilate sulfate and synthesise the DMSP precursors, cysteine and methionine; (ii) demethylate DMSP and generate methanethiol; (iii) cleave DMSP, generating dimethyl sulfide (DMS) and acrylate; and (iv) utilise or detoxify acrylate. The impacts of varied environmental factors (temperature, salinity, light and UV radiation) on S. aestuarii AMM-P-2 DMSP biosynthesis were characterised. DMSP levels in S. aestuarii AMM-P-2 increased almost two-fold under both hypersaline conditions (40 PSU) and high UV exposure. DMSP catabolism through the cleavage pathway also increased under these conditions, producing the antioxidants DMS and acrylate, a potential response to the oxidative stress generated. Overall, our results reveal that coral-associated bacteria can synthesize DMSP and may therefore contribute to DMSP production by the coral holobiont.